2010
DOI: 10.1139/g10-046
|View full text |Cite
|
Sign up to set email alerts
|

Complex prokaryotic genome structure: rapid evolution of chromosome II

Abstract: Although many bacteria with two chromosomes have been sequenced, the roles of such complex genome structuring are still unclear. To uncover levels of chromosome I (CI) and chromosome II (CII) sequence divergence, Mauve 2.2.0 was used to align the CI- and CII-specific sequences of bacteria with complex genome structuring in two sets of comparisons: the first set was conducted among the CI and CII of bacterial strains of the same species, while the second set was conducted among the CI and CII of species in Alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
4
11
0
Order By: Relevance
“…These results are in agreement with the study of Bavishi and colleagues [34], which indicated that chromosome 2 evolves faster than chromosome 1, leading to different conservation on inter- and intraspecies level. This global comparison also indicated that strain CH34 is more closely related to strains isolated from Congo than with the two other strains (CH42 and CH79) isolated in Belgium.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the study of Bavishi and colleagues [34], which indicated that chromosome 2 evolves faster than chromosome 1, leading to different conservation on inter- and intraspecies level. This global comparison also indicated that strain CH34 is more closely related to strains isolated from Congo than with the two other strains (CH42 and CH79) isolated in Belgium.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, rpoQ and its A. salmonicida homologue, VSAL_II0319 , are found on the smaller, second chromosomes of V. fischeri and A. salmonicida , respectively, where many paralogs and nonessential genes are also located (43). Such a position would be consistent with our hypothesis that rpoQ is a recently duplicated gene and diverged in the Vibrionaceae (44, 45). …”
Section: Discussionsupporting
confidence: 91%
“…Although it is not immediately clear which predominates, it is probably a combination of both situations. As hypothesized before [26], it is likely then that relaxed structural constraints on the CII of bacteria significantly contributes to their increased evolution and divergence compared to CI, although the findings of the current study may stand in contrast to that idea.…”
Section: Discussionmentioning
confidence: 46%
“…In R. sphaeroides 2.4.1, CII has been shown to be rapidly evolving [25,26]. For this reason, the second hypothesis was that gene paralogs on different replicons might have experienced different selective pressures within R. sphaeroides and specifically that paralogs between CI and CII might have experienced different levels of selection from those contained strictly within CI, within CII, or within plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation